Extracellular DNA in bacterial biofilms. Part I: origin - Krestetska, S (Annals of Mechnikov's Institute, 2020)
Significant number of chronic bacterial infections involves the biofilm formation, but regulation of this process is still far from beingwell understood. Some progress has been achieved since the reassessment of extracellular DNA (eDNA) functions in biofilm establishment and remodeling, including influence of this natural polymeric substance on mechanical stability and adhesiveness of extracellular polymeric matrix (EPM). As was shown eDNA can appear in EPM at different stages of biofilm development via different ways, including active secretion or assimilation from surrounding milieu, but the main source is widely considered to be induced cell death with subsequent lysis. Cell death induction as a kind of social behavior in prokaryotes seems to represents an essential part of the developmental program, clearly associated with a switch to a sessile community lifestyle and biofilm formation per se. Review is focused on mechanisms allowing controlled eDNA release, mainly on those underlying self- or hetero-destructive behavior in bacterial populations.